Imej kota dalam sastra oksidentalisme di Malaysia - Rahamad, M.S. (2010)
This study focuses on the images of the city in Malaysia’s literature, based on the postcolonial criticism perspective. It explores the question whether the city can be assumed as the evil element that needs to be fought because it creates the images of modernity influenced by the West. The texts chosen to be analyzed are limited only to novels in the 20s and 30s, when Tanah Melayu (the name before Malaysia is formed) was under the British colonialism. The findings suggest that the images of the city in the Occidentalism texts were not viewed as dichotomous since the authors also did not escape from being ambivalent.